Results of a long-term optical variability study of 11 quasars and VRI photometry of comparison stars - Minev, Milen; Trifonov, Trifon; Ivanov, Valentin D; Ovcharov, Evgeni; Bozhilov, Vladimir; Valcheva, Antoniya; Kostov, Andon; Nedialkov, Petko (Monthly notices of the Royal Astronomical Society, 2024)
We present the results of a 15-yr long-term optical monitoring of 11 quasars conducted with the 2-m Ritchey-Chretien-Coude and the 50/70 cm Schmidt telescopes at the Rozhen National Astronomical Observatory, Bulgaria. Our observations are performed with standard Johnson-Cousins V RI band filters and for each quasar we present a set of comparison standard stars that can be used for monitoring of objects in these fields (including finding charts for the stars identification). The variability and periodicity of each quasar are analysed individually and discussed. The physical properties of each quasar, such as their classification, redshift, and radio structures, are also discussed based on previous literature. Damped random walk model shows the best or the second best fit to the light curves of all objects. However, in six cases periodic models provide comparably good fits and make these six objects a valuable addition to the growing sample of quasars with periodic flux variation. They will be suitable for further investigation of the hitherto unclear mechanisms that give rise to this variability pattern. Our results provide important insights into the long-term variability and physical properties of quasars, which can further deepen our understanding of the nature and evolution of active galaxy nuclei.